Le faux-monnayage dans le Puy-de-Dôme du Second Empire à la Belle Époque : du mythe à la réalité - Sébastien Soulier (Criminocorpus)
The broadcast (emission, issue) and the counterfeiting money represent only 1,6 % of the business (affairs) judged by the criminal court of Puy-de-Dôme between 1852 and 1914, that is 54 defendants (accused) besides 60 years. Is it for all that an exceptional crime in the media sense (direction) of the term? The representation of the forgery - monnayage in the local press in the XIXth century and in the Belle Epoque has this of specific that it is subjected to two ideas that we are made of the crime, that of a mythical criminality printed by folklore and by mystery, and that of insignificant acts committed by individuals and in completely commonplace conditions, even insignificant. This reflection aims at approaching at once (at the same time) the media face (figure) of the counterfeiter in the puydomoise press and the social and occupational reality of this criminality from the Court decisions of assizes (conferences) of Puy-de-Dôme.